POPULATION DYNAMICS OF KAWAKAWA (Euthynnus affinis) LANDED AT PPI UJONG BAROH, WEST ACEH - Asri Mursawal; Sri Wahyuni; Anisa Mardhatila; Oktavia Oktavia; Fitri Diana; Serliana Hotmariska Marbun; Ronal Kurniawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study analyzed the population dynamics of kawakawa tuna (Euthynnus affinis) landed at PPI Ujong Baroh, West Aceh, from May to August 2025, using length-frequency data and the Von Bertalanffy growth model. A total of 815 individuals were measured to estimate growth, mortality, and exploitation parameters. The fork length ranged from 22–69 cm, dominated by medium-sized fish (30–37 cm FL), with the length at first capture (Lc = 33 cm FL) notably smaller than the length at first maturity (Lm ≈ 42–43 cm FL). Growth analysis indicated rapid juvenile growth, characterized by an asymptotic length (L∞) of 90 cm and a relatively high growth coefficient (K), while recruitment occurred periodically throughout the year. Mortality estimates showed total mortality (Z) of 4.77/year, natural mortality (M) of 1.45/year, and fishing mortality (F) of 3.32/year, resulting in an exploitation rate (E) of 0.70, which exceeds the optimal reference point (E = 0.5). These findings indicate that the kawakawa tuna stock in West Aceh is currently overexploited. This study provides the first updated, location-specific population parameter estimates for E. affinis in West Aceh waters, offering a critical scientific baseline for regionally adaptive fisheries management. Science-based management measures are therefore recommended, including implementing a minimum landing size of ≥43 cm FL, seasonal closures during spawning periods, effort control, and strengthened fisher participation to ensure long-term stock sustainability